Insight in bipolar disorder: a comparison between mania, depression and euthymia using the Insight Scale for Affective Disorders - Silva,Rafael de Assis da (2015)
Objective: To evaluate whether having general insight into bipolar disorder and its symptoms is affected by the mood state of the patient, using the Insight Scale for Affective Disorders, a hetero-application scale for people with mood disorders.Methods: Ninety-five patients with bipolar disorder were evaluated and divided into different groups according to the mood state presented during assessment (i.e., euthymia, mania and depression). Sociodemographic and clinical data (Hamilton Depression Scale, Young Mania Rating Scale, and Clinical Global Impressions Scale) were recorded. Insight was evaluated using the Insight Scale for Affective Disorders.Results: Patients with bipolar disorder in mania show less insight about their condition than patients in depression or euthymia, and less insight about their symptoms than patients with depression, with the exception of awareness of weight change.Conclusions: Loss of insight during mania may have important implications for treatment compliance and adherence and needs to be taken into account in the clinical management of people with bipolar disorder.